2021
DOI: 10.32936/pssj.v5i1.199
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of One-Stop Service Policy in Protecting the Rights of Indonesian Migrant Workers in Tulungagung

Abstract: The Indonesian government has tried to protect migrant workers, one of which is through Law no. 18 of 2017 concerning protecting the rights of migrant workers in an integrated manner. This research aims to examine how this policy’s effectiveness in protecting the rights of Indonesian migrant workers in Tulungangung Regency. This research uses descriptive research with a qualitative approach. The research findings show that one-stop service helps prospective workers manage all documents quickly and easily and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…This study found that there were institutions that had not been incorporated, causing ineffective services [8]. Meanwhile, Sulistyowati thinks that the existence of an integrated one-stop service can provide convenience for migrant workers [9]. Another research conducted by Samad stated that this program was able to develop government public services and should develop in other areas [10].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that there were institutions that had not been incorporated, causing ineffective services [8]. Meanwhile, Sulistyowati thinks that the existence of an integrated one-stop service can provide convenience for migrant workers [9]. Another research conducted by Samad stated that this program was able to develop government public services and should develop in other areas [10].…”
Section: Introductionmentioning
confidence: 99%